Porphyromonas gingivalis aggravates alcohol-related liver injury via gut microbiome-HO-1-ACSL4-dependent ferroptosis - Feng, Xuezhe; Wang, Yue; Zhu, Cheng; Huai, Qian; Cui, Juanjuan (Frontiers in Microbiology, 2025)
BackgroundAlcoholic liver disease (ALD) is a common liver condition caused by long-term alcohol consumption, and its specific molecular mechanism remains unclear. It may be influenced to some extent by ferroptosis and Porphyromonas gingivalis (P.g), which is an important pathogen of periodontitis.Materials and methodsC57BL/6 J mice and AML12 cells were selected as the study subjects. The periodontitis model was induced using P.g, and the alcoholic liver model was created. Pathological analysis was performed on the liver, intestine, and periodontal tissues. 16S rRNA sequencing was used to analyze changes in the intestinal flora and intestinal gap junction protein (zonula occludens-1 (ZO-1) and occludin) levels in each group. Ferroptosis indices were detected in the liver tissues and AML12 cells.ResultsOral exposure to P.g induced mice periodontitis and exacerbated alcohol-related liver injury. Both alcohol and P.g caused intestinal flora disturbance, damage to the intestinal epithelial barrier, increased permeability, and activation of mouse hepatocyte ferroptosis. Furthermore, P.g aggravated such alcohol-induced liver damage.ConclusionBoth alcohol and P.g can lead to intestinal flora disturbance, damage to the intestinal epithelial barrier, increased permeability, and the activation of mouse hepatocyte ferroptosis, and P.g can aggravate such alcohol-induced liver damage. Acyl-CoA synthetase long-chain family member 4 (ACSL4) and heme oxygenase-1 (HO-1) play important roles in the exacerbation of alcoholic liver injury by P.g.